SAPTALAKU: Penanggulangan Dampak Covid-19 Melalui Budidaya Perikanan Hulu ke Hilir Kelurahan Mangundikaran - Lukman Hakim; Septian Bima Fajar Prambudi; Ganevi Widya Wahyuningtyas (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
Coronavirus Disease (COVID-19) is an infectious disease caused by a newly discovered type of coronavirus. There are many impacts caused by the Covid-19 Pandemic, both in terms of health, economy, food and social issues. The village is a place that is protected from the spread of Covid-19, which is proven by several appeals not to go home so that families in the village avoid exposure to the Corona Virus. The area used as the place for this Community Service Program is in Mangundikaran Village, Nganjuk District, Nganjuk Regency which was held on July 7 to August 18, 2020. The purpose of this KKN-T is to increase food security and social society independently due to the impact of the Covid-pandemic. 19 through the SAPTALAKU program with upstream to downstream aquaculture. The activities of making tarpaulin ponds, giving fish seeds, and providing fish feed are the starting points for the cultivation of small fish that can be carried out by every family or household. However, it needs to be considered in terms of pond placement because this can affect fish development. After that, the results of fish farming are processed into nuggets which become an attraction to be used as additional business. Keywords: fish farming, Mangundikaran, Saptalaku